Preterm labour management--an evidence--update - Piyamongkol W. (2014)
Preterm birth is the leading cause of perinatal mortality and morbidity. Biologic markers, fetal fibronectin and transvaginal ultrasound scanning, have been introduced to identify the risk of preterm birth. The aim of management of preterm labour is to reduce neonatal complications. Various groups of tocolytic agents have been used, including beta-adrenergic agonists, calcium channel blockers, magnesium sulphate, prostaglandin synthetase inhibitors and oxytocin receptor antagonists. Beta-adrenergic agonists, the most widely used tocolytic agent, seem to show significant serious side effects. Calcium channel blockers and oxytocin receptor antagonists provide comparable efficacy to beta-adrenergic agonists, while giving fewer adverse effects. However calcium channel blockers are cheaper and more convenient to administer During 28-34 weeks of gestation, it is recommended to use tocolytics just for the first 24-48 hours waiting for fetal lung maturity after corticosteroid treatment or in utero transfer. Maintenance therapy of tocolytics is not useful in prolongation of pregnancy and does not improve perinatal outcomes. After 34 weeks of gestation there is no benefit of prolongation of the pregnancy. A single course of corticosteroid treatment is effective in preventing respiratory distress syndrome during 28-34 weeks of gestation. However, repeated treatment as a weekly course seems to do more harm than good.